2021
DOI: 10.1080/23311908.2021.1988193
|View full text |Cite
|
Sign up to set email alerts
|

Effective coping strategies employed by university students in three sensitivity groups: a quantitative text analysis

Abstract: People differ in their sensitivity to internal and external stimuli, falling into one of three sensitivity groups (low, medium, and high). Studies have pointed out that individual differences in sensitivity should be considered in psychological intervention settings. This study aimed to explore effective coping strategies in the three sensitivity groups. In total, 692 Japanese university students (389 females; M age = 20.6 ± 1.4 years) responded to an open-ended question about the coping strategies they employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 62 publications
0
8
0
2
Order By: Relevance
“…At the time of the first survey (November 2020), they had about 5.4 million web survey monitors all over Japan. Many researchers have collaborated with the company to collect data (Yano et al, 2021a), suggesting the high quality and reliability of their data. The respondents were given points exchangeable for cash as rewards if they completed a questionnaire online.…”
Section: Participants and Proceduresmentioning
confidence: 99%
See 3 more Smart Citations
“…At the time of the first survey (November 2020), they had about 5.4 million web survey monitors all over Japan. Many researchers have collaborated with the company to collect data (Yano et al, 2021a), suggesting the high quality and reliability of their data. The respondents were given points exchangeable for cash as rewards if they completed a questionnaire online.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…Lionetti et al 's (2022) empirical investigation supported this assumption, while emphasizing the moderating role of the parenting environment. Additionally, the results of an open-ended survey conducted to explore the characteristics and effectiveness of coping strategies among university students with high and low sensitivity (Yano et al, 2021a) indicated that although strategies related to emotion regulation were extracted in all the sensitivity groups, their associations with mental health partly differed between the groups. Specifically, while positive thinking (similar to positive reappraisal) may be more effective for individuals with higher sensitivity, it may be important for lower-sensitivity individuals to receive emotional and instrumental support from friends who understand their feelings and offer useful advice.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, emotional-focused coping strategies have a significant effect on controlling emotions and are the key to improving cognitive, affective, motivational abilities (Basith et al, 2021), while problem-focused coping strategies can make a person have the ability to overcome a problem (Muthmainah et al, 2021). A recent study reported that coping strategies are the key to dealing with all problems that often arise during the current COVID-19 pandemic (Yano et al, 2021). Coping strategies are able to change threats into challenges, so that they can increase faith and self-confidence, students are more motivated and able to control the situation becomes more conducive (Litwic-Kaminska, 2020).…”
Section: Impact Of Coping Strategies On Anxietymentioning
confidence: 99%